Are Current Seedling Demographics Poised to Regenerate Northern US Forests?. Issue 6 (28th August 2019) - Vickers, Lance A; McWilliams, William H; Knapp, Benjamin O; D'Amato, Anthony W; Dey, Daniel C; Dickinson, Yvette L; Kabrick, John M; Kenefic, Laura S; Kern, Christel C; Larsen, David R; Royo, Alejandro A; Saunders, Michael R; et al.
Abstract: Securing desirable regeneration is essential to sustainable forest management, yet failures are common. Detailed seedling measurements from a forest inventory across 24 northern US states were examined for plausible regeneration outcomes following overstory removal. The examination included two fundamental regeneration objectives: 1) stand replacement- securing future forest and 2) species maintenance- securing upper canopy species. Almost half the plots lacked adequate seedlings to regenerate a stand after canopy removal and over half risked compositional shifts. Based on those advance reproduction demographics, regeneration difficulties could occur on two-thirds of the plots examined. The remaining one-third were regeneration-ready. However, compared to historical norms, increased small-tree mortality rates reduces that proportion. Not all forest types rely on advance reproduction and results varied among the forest types examined. Some variability was associated with browsing intensity, as areas of high deer browsing had a lower proportion of regeneration-ready plots.